Acute Oral Toxicity Assessment of Repchol in Wistar Rats: A Liver-protective Herbal Premix for Poultry - M., Tripura; M.G., Vaidya; S.A., Belkhede; S.C., Damekar; S., Gupta; S.W, Hajare (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The present study was conducted for the assessment of acute oral toxicity and safety analysis of Repchol Premix (M/s Ayurvet Limited) according to OECD-423 guidelines. Six adult Wistar rats, weighing 113-134 g, were used for the study. After oral administration of Repchol@ 300 and 2000mg/kg body weight, the animals were observed for manifestation of toxic effect and death upto14 days. Evaluation of safety analysis and toxicity was assessed on the basis of presence of mortality or toxicity symptoms. Every animal in group served as its own control. At the end of experiment blood biochemical parameters and histopathological changes in heart, liver, kidney and lung were studied. The results showed that Repchol did not produce toxic effects or mortality during the experimental period. The body weight changes observed for two weeks were in the normal range. In Repchol treated rats biochemical parameters like AST, ALT, ALP and creatinine were observed within normal range and in histopathological examination no significant microscopic alterations were observed. Thus, the observations indicated that Repchol Premix did not produce toxic effect or acute oral toxicity and the LD50 of compound is beyond 2000mg/kg.